China's rebalancing and gender inequality - Brussevich, Mariya,Dabla-Norris, Era,Li, Bin (International Monetary Fund, 2021)
This paper examines gender inequality in the context of structural transformation and rebalancing in China. We document declining women's relative wages and labor force participation in China during the last two decades, despite rapid growth and expansion of the service sector. Using household data, we provide evidence consistent with a U-shaped relationship between economic development and women's labor market outcomes. Using a model of structural transformation, we show that labor market barriers for women have increased over time. Model counterfactuals suggest that removing these barriers and increasing service sector productivity can boost both gender equality and economic growth in China
10.5089/9781513573779.001
Keywords: Graue Literatur; structural transformation; household data; labor force participation; gender inequality; Economics Of Gender; Foreign Exchange; Informal Economy; Non-Labor Discrimination; Underground Econom; Women''s Studies'; Industries: Service; Economics: General; Gender Studies; Wages; Compensation; and Labor Costs: General; Industry Studies: Services: General; Demand and Supply of Labor: General; Labor Standards: Labor Force Composition; Economic & financial crises & disasters; Economics of specific sectors; Gender studies; women & girls; Labour; income economics; Social discrimination & equal treatment; Economic growth; Financial crises; Economic sectors; Gender; Macroeconomics; Labor; Services sector; Labor supply; Currency crises; Informal sector; Economics; Women; Sex discrimination; Wages; Labor market; Service industries